Optimization of Ganoderma lucidum Mycelium Production for Biomaterial Production on Solid Medium with Bamboo and Empty Palm Oil Bunch Variation - Mustika Dewi; Rakha Pradipa Bhagaskara Susanto; I Nyoman Pugeg Aryantha (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
The chemical composition of sengon wood is ideal for the nutritional needs of fungi, particularly wood fungi. Fungi obtain their energy by degrading the lignocellulosic components (cellulose, hemicellulose, and lignin) found in wood. Although sengon is an excellent substrate, its availability is limited, and its price continues to rise. Potential alternative cultivation media include bamboo and oil palm, which are the natural habitats of Ganoderma lucidum. This study investigates the potential of bamboo sawdust and shredded empty palm oil fruit bunches (EFB) as alternative substrates for growing G.lucidum. Currently, G. lucidum is cultivated using a cereal-based medium with sengon sawdust waste. This study examines the growth of G. lucidum in media containing bamboo sawdust and EFB as an alternative media derived from organic waste. The experiment involves three stages: inoculating G. lucidum into media with varying concentrations of bamboo sawdust and EFB, adapting the fungus to complex media with different concentrations of these materials, and finally substituting sengon sawdust with bamboo sawdust or EFB in a control medium to observe growth parameters. The results showed that most media supplemented with bamboo sawdust and EFB, except for the 2% and 4% bamboo sawdust concentrations in the first stage, significantly increased growth (p < 0.05). However, in the second stage, only certain concentrations (25% bamboo sawdust and 50% EFB) achieved the same growth rate as the control. In the third stage, G. lucidum in media modified with bamboo showed significantly faster growth, although the loss of organic matter was not significantly different. Although bamboo and EFB did not increase the biomass production of G. lucidum mycelium both showed potential as alternatives. These findings indicate that these materials are suitable for use as a growth medium for G. lucidum.